The unsolved mystery of UFOs - Sievert, Terri (North Mankato, Minn. : Capstone Press, 2013)
"Presents the mystery of UFOs, including current theories and famous examples"--Provided by publisher.
An object in the sky -- History and legend -- UfO or not? -- Searching for UFOs.
Includes bibliographical references (p. 23) and index.
Keywords: Unidentified flying objects -- Juvenile literature